The art of keeping cool - Lisle, Janet Taylor. (Atheneum Books for Young Readers, 2000)
In 1942, Robert and his cousin Elliot uncover long-hidden family secrets while staying in their grandparents' Rhode Island town, where they also become involved with a German artist who is suspected of being a spy.